PENGARUH WORK LIFE BALANCE DAN DUKUNGAN SOSIAL TERHADAP PSYCHOLOGICAL WELL BEING PADA KARYAWAN DI PERUSAHAAN DIGITAL MARKETING PT X YOGYAKARTA - Latifah Azzahra Zahira; Yasin Syarif Hidayatullah (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
The dynamic digital marketing industry at PT X Yogyakarta triggers mental stress due to high workloads, thus threatening the psychological well-being of employees. This study focuses on examining the influence of work-life balance and social support on the psychological well-being of the company's staff. The research steps used a quantitative approach with a convenience sampling technique on 122 respondents as a representative sample. The research stages included distributing a validated Likert-scale questionnaire and analyzing it using multiple linear regression to examine the relationship between variables. The quantitative research findings indicate that both factors simultaneously have a significant effect on psychological well-being (p = 0.001) with a contribution of 10.2 percent. Partially, only social support has a significant effect (p = 0.000), while work-life balance does not show a significant independent effect (p = 0.935). The majority of respondents (97.5%) have a moderate level of psychological well-being. The main conclusion confirms that social support in the workplace is a key pillar supporting employee mental health in facing the rapid rhythm of the industry. Companies need to prioritize developing a collaborative work climate and interpersonal support systems to increase staff resilience and professional dedication. These findings provide a basis for human resource management policies that are more responsive to workers' emotional needs to ensure the sustainability of organizational productivity in a comprehensive and sustainable manner in the future.